Expression of recombinant thermus aquaticus dna polymerase gene - Thanabalan, Asha a/p (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Taq DNA polymerase derived from the extreme thermophillic microorganism, Thermus aquaticus is very useful in Polymerase Chain Reaction (PCR) in which high temperature stable Deoxyribonucleotide acid (DNA polymerase is needed in amplifying a specific DNA fragment. It is also useful in DNA sequencing. For this purpose, many techniques of cloning and expression of this enzyme were practiced to obtain a high performance enzyme. The purification methods were designed to retrieve a high enzyme yield. In this method, we have tried to express the recombinant Taq Pol I enzyme in different expression systems to select the best host for the protein expression. The host BL-21 was selected because of the additional property within it, a plysS plasmid for tighter protein expression but simpler purification method as adapted from Grimm et. al (1995). Protein expression was induced over a 12 hour period using IPTG before it was viewed in a large SDS- PAGE. There were bands along a marker indicating a complete protein expression as the weight of Taq DNA polymerase is 94 kD.